Preliminary note on the fungal problem of rubber wood - Gnanaharan R (International Research Group on Wood Preservation Working Group III: Preservatives and Methods of treatment, 14th Annual Meeting, 9-13 May 1983, 1983)
Susceptibility of rubber wood to fungal attack limits its wider utilisation. Fungal problems encountered in treating rubber wood with boron compounds by diffusion process have been discussed. Sodium pentachlorophenoxide and 2-thiocyanomethylthio benzothioazole (TCMTB) were investigated for possible control of fungal growth during diffusion storage and their performance has been reported.
Keywords: Boron diffusion; Rubberwood